The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.30659/jpsa.v14i2.3870
|View full text |Cite
|
Sign up to set email alerts
|

Pembentukan Ruang Aktivitas Sosial Pada Ruang Terbuka Publik Taman Menteri Supeno

Abstract: The Menteri Supeno Park is one of the  grounds are among the active line meeting Menteri Supeno Street, Mugas Street and Pahlawan Street. A strategic location to the City Centre makes the Park is used for a variety of activities such as art, social activity, livelihoods, recreation and culture. The interconnectedness of activities in the public space is important to sustained beauty and tranquillity, let alone see the existence of the Park is located between the areas of trade, education and office. The Park h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…During activities in city parks, people are often influenced by their behavior in using the spaces (Aggita et al, 2019;Rita, 2017). Zeisel (1984) reported that there is a relationship between human behavior and spatial attributes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…During activities in city parks, people are often influenced by their behavior in using the spaces (Aggita et al, 2019;Rita, 2017). Zeisel (1984) reported that there is a relationship between human behavior and spatial attributes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Outdoor activities have also become a popular choice for individuals during the pandemic (Doubleday et al, 2020;Lai et al, 2020). Furthermore, city parks typically consist of various outdoor spaces that are designed for specific activities systems (Aggita et al, 2019;Bunakov, 2019;Rita, 2017). These spaces are interconnected within a spatial layout system and serve as locations for various engagements.…”
Section: Introductionmentioning
confidence: 99%